Automation Efforts in Public and Privately Owned University Libraries in the South-West of Nigeria (2018)
The concept of library automation is gradually gaining ground in Nigerian Libraries, particularly in the public and privately owned University libraries in the South-West part of Nigeria which is the focus of this study. The study examines automation efforts in Public and Privately Owned University Libraries (PPOULs) in the South- West, Nigeria. The study also identifies PPOULs that have been automated, the type of integrated library system(ILS) being used, its description, modules already activated, evidence ofzveb presence of these university libraries and the common challenges being faced by these university libraries in implementing automation, among others. Structured questionnaire was designed, using Google form with a link to elicit information from the respondents. The questionnaire was sent to the Systems Administrator/ Librarian of each of the libraries via email. The response rate was hundred percent (100%).The data were analyzed using frequency counts and percentages which are presented in tables. The results of the findings showed that more than half (61.5%) of PPOULs in the South-West were automated; using either proprietary, open source or in-house developed Integrated Library System (ILS). The finding also revealed that Koha ILS is used by 50% of the university libraries in the South-West Nigeria. Cataloguing module was found to be implemented by all the libraries while serials module is the least implemented among the libraries studied. The major challenges indicated are that of erratic power supply, insufficient staff to carry out automation project and insufficient fund to maintain automation project. The study concludes that automation has a growing list of benefits, particularly when it is adopted and implemented in the university academic libraries. The initiative will enhance effective information sendees delivery and at the same time raise the profile and prestige of the library and the university it semes.